TGF-β Signaling Methods and Protocols - Feng, Xin-Hua; Xu, Pinglong; Lin, Xia (Methods in Molecular Biology, 2016)
This volume details up-to-date information and attempts to take the reader into the exciting realm of TGF-β from the basic principles to the practical applications. Chapters provide basic introduction of TGF-β signaling from the cell surface to the nucleus, methods and techniques for the investigation of TGF-β signaling mechanism including receptors, Smads, intracellular kinases, microRNA, epigenetic regulation, post-translational regulations, non-Smad pathway; the physiological implications including those in cell cycle arrest, epithelial-mesenchymal transition, endothelial cells, adipogenesis, Th differentiation, stem cell, bone remodeling, ovary, zebrofish development, and frog animal capping; and the methodologies including metastasis imaging, 3D morphogenesis, membrane receptor quantification, conditional knockout, bone remodeling, kinase and phosphatase assays, BiFC interaction assays, and genome-wide siRNA screen. Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and key tips on troubleshooting and avoiding known pitfalls.   Authoritative and practical, TGF-Beta Signaling: Methods and Protocols aims to ensure successful results in the further study of this vital field